STRATEGIC DECISION-MAKING IN TUITION-FREE ISLAMIC SCHOOLS FUNDED BY BOS ASSISTANCE PROGRAMS - Ade Mamah Suryamah; Siti Nuraeni; Anis Zohriah; Apud Apud (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to analyze the process of strategic decision-making in the management of Islamic schools that do not charge tuition fees (SPP) and rely on the School Operational Assistance Fund (BOS) as the main source of funding. The focus of this research is to understand how policies and important decisions are made by school management in dealing with various resource limitations. The research method used is a qualitative approach with data collection techniques through interviews with teachers at SDIT Bani Daud Curug-Kota Serang. Through this method, the researcher obtained a deeper understanding of decision-making practices that occur within the school environment. The results of the study indicate that teachers are actively involved in the decision-making process through deliberation forums and regular school meetings. In these forums, teachers have the opportunity to express their opinions, provide input, and offer solutions to various problems faced by the school. This participation reflects the implementation of participatory management, which provides opportunities for educators to contribute to determining school policies. In addition, the implementation of flagship programs such as the Qur’an memorization (tahfidz) program has been running well due to the support and active role of teachers in guiding and motivating students. However, the school also faces several challenges, particularly the limitations of facilities and infrastructure such as sports facilities, as well as limited resources due to the absence of tuition fees. Therefore, a participatory and deliberation-based decision-making model becomes an important strategy in maintaining the sustainability of educational programs in schools with limited funding.